Luminescent properties of combustion synthesized BaAl2O4:Eu²+ and (Ba1-xSrx)Al2O4:Eu²+ phosphors co-doped with different rare earth ions - Annah, Lephoto Mantwa (University of the Free State, 2011)
A Combustion method was used to prepare all the alkaline earth aluminates (rare-earths doped BaAl2O4, BaSrAl2O4 and BaZnAl2O4) phosphor powders in this study. Measurements of these phosphor powders were carried out using various characterization techniques such as X-ray diffraction (XRD), Scanning Electron Microcopy (SEM), X-ray energy dispersive spectroscopy (EDS), X-ray Photoelectron Spectroscopy (XPS) and Fourier Transform Infrared Spectroscopy (FT-IR). The XRD data were collected using a D8 advance powder X-ray diffractometer with CuKα radiation. Morphology and elemental composition were done using JEOL- JSM 7500F Scanning Electron Microscope. The stretching mode frequencies data were collected using Perkin Elmer Spectrum 100 FTIR spectrometer and the elemental composition on the surfaces of the phosphor powders were monitored by the PHI 5400 Versaprobe scanning X-ray photoelectron spectrometer. Photoluminescence (PL) data were collected using 325nm He-Cd laser and decay data were collected using Varian Cary Eclipse Fluorescence Spectrophotometer coupled with a monochromatized Xenon lamp (60-75 W) as excitation source and measurements were carried out in air at room temperature. The thermoluminescence (TL) data were collected using a Thermoluminescence Reader (Integral-Pc Based) Nucleonix TL 1009I. BaAl2O4:Eu2+ phosphor powders co-doped with different trivalent rare-earth (RE= Dy3+, Nd3+, Gd3+, Sm3+, Ce3+, Er3+, Pr3+ and Tb3+) ions were prepared at an initiating temperature of 600oC and annealed at 1000oC for 3 hours. The X-ray diffraction (XRD) data shows hexagonal structure of BaAl2O4 for both as prepared and post annealed samples. All samples exhibited bluish-green emission associated with the 4f65d1→4f7 transitions of Eu2+ at 504 nm. The longest afterglow was observed from the BaAl2O4:Eu2+ co-doped with Nd3+. BaAl2O4:Eu2+, Nd3+, Gd3+ phosphor powders were prepared at different initiating temperatures of 400-1200oC. X-ray diffraction data show the formation of the hexagonal BaAl2O4 structure at the temperatures of 500oC-1200oC. The crystal size calculated from the phosphor powder prepared at 1200oC was found to be 63 nm. Blue-green photoluminescence with persistent/long afterglow, was observed at 502 nm and the highest PL intensity was observed from the sample prepared at 600oC. The phosphorescence decay curves showed that the rate of decay was faster in the case of the sample prepared at 600oC compared to that prepared at 1200oC. The TL glow peaks of the samples prepared at 600oC and 1200oC were both stable at 72oC suggesting that the traps responsible for the long afterglow were not affected by the temperature. Barium-substituted phosphor powders of (Ba1-xSrx)Al2O4:Eu2+;Nd3+ composition were prepared at an initiating temperature of 500oC. The X-ray diffraction with the composition of x = 0 shows the hexagonal phase of BaAl2O4 and the one for x = 1 shows the monoclinic phase of SrAl2O4. The XRD with the composition of x = 0.4, 0.5 and 0.6 shows the admixture of BaAl2O4 and SrAl2O4 structures. SEM investigations showed some changes on the surface morphology for different compositions. Photoluminescence (PL) studies showed the (Ba1-xSrx)Al2O4:Eu2+;Nd3+ (x = 0) and (Ba1-xSrx)Al2O4:Eu2+;Nd3+ (x = 1) with blue-green to bright-green emissions with peaks at 505 nm and 520 nm respectively. The mixed composition with x = 0.4, 0.5 and 0.6 showed two peaks at 447 nm and 517 nm. Phosphorescence showed higher luminescence for (Ba1-xSrx)Al2O4:Eu2+;Nd3+ at (x = 0) compared to other compositions. (Ba1-xZnx)Al2O4:Eu2+;Nd3+ phosphor powders with the compositions x = 0.2, 0.4, 0.5, 0.6, 0.8 and 1 were prepared at an initiating temperature of 500oC. The X-ray diffraction showed the cubic structure for the compositions of x = 0 and x = 1. The SEM images of the phosphor samples showed different kinds of morphologies for the compositions x = 0, 0.5 and 1. The PL emission of the phosphor powder clearly showed a shift from green to blue regions. The highest PL emission and the long afterglow ascribed to trapping and detrapping of charge carriers were observed from (Ba1-xZnx)Al2O4:Eu2+;Nd3+ with x = 0.2.
Dissertation (M.Sc. (Physics))--University of the Free State, 2011
Keywords: Photoluminescence; Combustion method; Thermoluminescence; Long afterglow; Rare earth ions; Alkaline earth aluminates; Self-propagating high-temperature synthesis; Alkaline earth compounds -- Synthesis